Open design in practice : designers in residence Kortrijk - Bouchez, Hilde, 1967-; Van Durme, Jessy, ....- (Kortrijk : Designregio Kortrijk, 2015)
The Open Design methodology and the experiences of the 3 Designers in Residence Kortrijk 2014 were compiled in the publication Open Design in Practice! The publication will be distributed from January 2016 by Luster. The ‘Designers in Residence Kortrijk' project was created with the aim of giving the Kortrijk creative region an international reputation as an innovating centre in Europe. With ‘Open Design' as a general theme and ‘design for a better connected community' as a specific starting point, the project intends to lower the threshold between design and daily life. ‘Open Design in Practice' is not a specific response to questions from the community, but rather an exploration of potential, opportunities and obstacles within a contemporary community. The designer responds to these: he can anticipate, deliver insights and propose solutions, not just for enterprises or the city, but just as much for you and me.